NETNOGRAPHIC STUDY OF ONLINE GENDER-BASED VIOLENCE (KBGO) ON TWITTER - Rita Lismini; Sri Narti; Vethy Octaviani (Sean Institute, 2023)
Online Gender Based Violence (KBGO) is a form of gender injustice and discrimination that occurs in the online space. KBGO is very dangerous, because many online spaces do not have enough regulations to protect someone from this type of violence. This study aims to determine online gender-based violence through online sexual harassment (Cyber Sexual Harassment) on Twitter. This study uses the theory of CMC (Computer Mediated Communication), and the type of research used is qualitative research using netnography methods. The results of this study indicate that there are six categories of cyber sexual harassment, the first is direct threats of sexual or physical violence which are all attempts, both physical and verbal, that lead to sexuality or sexual organs of a person without obtaining consent and having elements or threats. Second, online harassment is an act of sexual harassment through unwanted messages, attention and contact or things that intend to embarrass the victim. Third, harsh comments are w negative words that can even be read or shared by otherswithout censorship. The four utterances of sex hatred are acts of inviting and even spreading untruths of news which makes it possible to influence other people on social media to influence other people regarding the act of spreading negative content. The fifth is victim blaming, namely the perpetrator tries to make the victim feel continuous negative attacks on social media and the sixth is the use of indecent images is an act of spreading inappropriate things that should not be shared on social media, especially Twitter. In this study, the researcher suggests that Twitter social media users should limit and stop sharing things that are cyber sexual harassment and the researcher also hopes that this study can become a reference in the future and can be of benefit to society and social media users to increase knowledge, regarding online gender-based violence education on social media Twitter